The Moderating Effects Of Enterprise Risk Management (Erm) On Managerial Ownership, Leverage, And Company Growth On Company Value In The Financial Industry Sector Listed On Indonesia Stock Exchange 2015-2019 - Geo Fanny Aprilia; Rudolf Lumban Tobing; Lambok DR Tampubolon (Fakultas Bisnis, 2022)
This study is a research gap from previous studies due to differences in results between researchers. This study discusses the effect of managerial ownership, leverage, and firm value with enterprise risk management as a moderating variable in financial sector companies listed on the Indonesia Stock Exchange in 2015-2019. This study took a sample of 17 companies with a total of 85 units of analysis. In processing the data, the researcher used the SPSS Version 22 program.The results of this study indicate that managerial ownership has no significant effect on firm value. While leverage has a significant negative effect on firm value and firm growth has a significant positive effect on firm value. ERM does not significantly moderate managerial ownership on firm value. ERM significantly moderates the effect of leverage and firm growth on firm value.